Caring for people with disability and human growth: evolutionary perspectives and contribution to psychological wellbeing - Bernacer, Javier (Frontiers in Psychology, 2024)
From an evolutionary point of view, organisms with mutations resulting in maladaptation are an unavoidable result of genetic variability, and they do not usually survive natural selection. Thus, they do not produce benefits for the species. I contend that this is different in humans at two levels. First, the existence of people with disability has been essential for human growth as a species. Human ancestors' evolving cognitive and social abilities were boosted by caring for vulnerable members of the species, including premature offspring and people with disability. Therefore, caregiving was an essential trait of the evolution of humans, intertwined with the development of bipedalism, the hand, face, vocal apparatus, and brain. Second, caring for disability is also a source of growth at a personal level. Even though most scientific literature focuses on the stress and burden caused by caring for people with disability, there is solid evidence to accept caregiving as a source of happiness and flourishing for human beings. Hence, disability still has an essential role in improving human life nowadays. Contrary to this evidence, influential utilitarian bioethicists promote the elimination of disability from modern societies. Following the arguments presented here, this will lead to the withering of society. In conclusion, disability should be acknowledged as an essential source of growth for the human species.